Which Regions Benefit from New Rail Accessibility? Germany in 2030. - Wenner, Fabian; Thierstein, Alain (Taylor & Francis, 2020)
New transport infrastructure alters the spatial distribution of accessibility, which can influence a region’s development potential. The implementation of High-Speed Rail (HSR) during the last decades has often considerably improved rail accessibility of connected regions, but is also often found to increase relative discrepancies between regions. We analyse the effects of currently planned rail projects on regional accessibility in Germany, with a spatial and network structure differing from other countries, for the year 2030. We use a population potential and a degree centrality measure and find slight tendency towards greater balancing of accessibility across regions and greater poly-centralisation within the rail network, showing the importance of network integration and improvements beyond the HSR network. Two macro-regions of Germany profit most from the planned rail lines: the economically dynamic South and the catching-up East. We interpret this as the outcome of two simultaneous planning goals which include removing “bottlenecks” and supporting weaker regions. We propose that the official regional planning assessment currently used in the planning process of national rail infrastructure could be improved by applying a potential accessibility measure.
Keywords: Verkehrsinfrastruktur; Schienenverkehr; Hochgeschwindigkeitsnetz; Verkehrsanbindung; Erreichbarkeit; Regionale Disparität; Raumordnung; Regionalplanung